Extraction of manganese from Indonesian manganese ore using sugarcane bagasse-acid reductive leaching - Widi Astuti; Pinania, Kherani Hana; Lesmana, Donny; Dewi, Jilda Sofiana; Supriyadi, Harry; Sumardi, Slamet; Prakosa, Agus (Jurnal Rekayasa Proses, 2025)
In this study, sugarcane bagasse was used as a reducing agent in manganese leaching from manganese ore from Way Kanan, Lampung under acidic conditions using sulfuric acid as a leaching reagent. Bagasse is an agricultural waste from the cane sugar manufacturing industry which is commonly found in Lampung Province. This agricultural waste has the potential to become a reducing agent in manganese leaching because it contains carbon in the form of cellulose and sugar. The optimization of the leaching conditions has been investigated with the parameters of H2SO4 concentration, temperature, and pulp density. The highest manganese leaching recovery was obtained under the following optimized conditions: 1 M H2SO4 concentration, 14 g sugarcane bagasse/20 g MnO2, 50 g/L pulp density, 80 °C leaching temperature, 200 rpm stirring rate, and 4 hours of reaction time. The present process therefore deals with achieving the effective recovery of value-added products from low-grade manganese ore using agriculture waste as reducing agent.